Analisis Posisi Iklan Banner pada Situs Web Berita Online Terhadap Klik dan Ad Recognition - Oktavia Zalma; Ismiarta Aknuranda; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Online advertising, especially banner ads, is a major source of cash flow on many websites that provide free services to its users, one of them is an online news website. However, banner ads have a tendency to be ignored or avoided by internet users, resulting in the objective of the advertiser not being achieved and the owner of online news websites are not getting the maximum revenue stream. Therefore, this study aims to find out the position of an effective banner ad, viewed from click-trough rate and ad recognition of each of eight positions banner ads contained on the online news website in general. This research uses descriptive qualitative method with user testing and questionnaire technique. The result of this study is a description of user behavior pattern toward click-through rate and ad recognition so that it can generate recommendations of effective banner ads position. From this study, it can be known that the fastest ad position in attracting visitors and has the most number of clicks is floating on the right edge, the position that most likely to be ignored is on the bottom left, the position that has the highest ad recognition is on bottom right, and the position that most remembered by visitors in clicking an ad is floating on the left edge.